PERAN PERUM BULOG DALAM PEMASARAN BERAS DI KABUPATEN WAJO - Ma'ruf, Muhammad Imam (Jurnal Social Economic of Agriculture, 2019)
The purpose of this research is to analyze the marketing margin of rice that generated by farmers on Belawa, Wajo Regency, South Sulawesi Province. This research used cross-section data based on the time dimension. This research used snowball sampling to determine the sample. There are 25 people as respondent sample. This study used in-depth interview method, and analysis tools such as marketing’s margin function, classic assumption test, F-test, and t-test. Public Corporation Logistics Agency (Bulog) acts as a provider of rice in the form of realization to meet food. Bulog is expected to control the supply and distribution of grain and rice in region IV of Wajo sub-division. There are four grain/rice marketing channels on Belawa, Wajo Regency, South Sulawesi Province. Bulog has not played a sufficient role in the grain/rice marketing channel on Belawa, Wajo Regency, South Sulawesi Province; even though the highest marketing margin is Rp 4,167/kg with a 52.75% farmer share.Keywords: Bulog, Marketing, Rice.